A A Perception of Samarinda Citizen in Choosing Zakat, Charity, and Shadaqah Institution - Tikawati Tikawati; Bambang Iswanto (Al-Tijary, 2021)
Samarinda is one of the most populous cities in East Kalimantan province. Some data which obtained from the Central Statistics Agency of Samarinda, they were recorded more than one million people living here until 2020. Meanwhile, around 80% of the population of Samarinda were Muslim. One of the pillars of Islam that is always done regularly every year is paying zakat. By considering the large population in Samarinda, the potential for zakat in this city is very large. Professional management of zakat infaq and shodaqoh potential will be an economic strength in order to reduce poverty level, create jobs, increase income and encourage people's economic growth.